Polyphosphate degradation by Nudt3-Zn2+ mediates oxidative stress response - Bàrbara Samper-Martín (Elsevier, 2021)
Summary: Polyphosphate (polyP) is a polymer of hundreds of phosphate residues present in all organisms. In mammals, polyP is involved in crucial physiological processes, including coagulation, inflammation, and stress response. However, after decades of research, the metabolic enzymes are still unknown. Here, we purify and identify Nudt3, a NUDIX family member, as the enzyme responsible for polyP phosphatase activity in mammalian cells. We show that Nudt3 shifts its substrate specificity depending on the cation; specifically, Nudt3 is active on polyP when Zn2+ is present. Nudt3 has in vivo polyP phosphatase activity in human cells, and importantly, we show that cells with altered polyP levels by modifying Nudt3 protein amount present reduced viability upon oxidative stress and increased DNA damage, suggesting that polyP and Nudt3 play a role in oxidative stress protection. Finally, we show that Nudt3 is involved in the early stages of embryo development in zebrafish.